Circonscrire les gisements de biomasse-énergie pour protéger l'alimentation et la biodiversité : le défi intenable - Yves Poinsot (Éditions en environnement VertigO, 2015)
By transfering assignment of substances or lands, the biomass energy file development creates competition with food and biodiversity functions of lands. It is therefore recommended to separate fields, producing second generation biofuels from woody biomass, sometimes prohibiting the use of corn in biogas digesters, and reserving energy crops to marginal lands. But these attempts to separate face an inevitable permeability between resources reservoirs. For biogas, it follows games on changes of time reserved for food and energy crops in plots, at time scale of a crop cycle or interannual rotations. In the forest, the duration of revolutions is shortened by short rotation coppice that connect industry and land, agricultural and forest. On the markets, changes in status of energy byproducts, becoming joint-products then major products when prices increase, plays the same role. In rural areas, the definition of marginal land that could be reserved for energy crops faces the very approximate limits of the concept. Beyond, biofuel industry using coal to produce fertilizer connects to fossil industry: their CO2 emissions present similar values.